High-temperature-resistant conductive paste as well as preparation method and application thereof
By optimizing the formulation of conductive paste, combining polyurethane resin, epoxy resin and specific conductive powders, the problem of conductive paste decomposition in high temperature environments is solved, and the effects of high heat resistance, flexibility and adhesion are achieved.
Patent Information
- Application Number
- CN202411912820.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing conductive paste is easily decomposed under high temperature environments, resulting in a degradation of performance and difficulty in taking into account both flexibility and heat resistance.
By optimizing the formulation, polyurethane resin and epoxy resin are used as the resin system, and the specific treatment of conductive powder and liquid polyol resin are added, combined with specific curing agents, rheology agents and coupling agents, a complex crosslinking network structure is formed to improve adhesion and heat resistance.
The conductive paste has achieved significant improvements in heat resistance, flexibility and adhesion, and can maintain stable performance in high temperature environments.
Smart Images

Figure BDA0005206157700000101 
Figure BDA0005206157700000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, and in particular to a high temperature resistant conductive paste and a preparation method and application thereof. Background Art
[0002] In recent years, electronic additive manufacturing technology, as a cutting-edge production process, has received widespread attention from the manufacturing industry. Among them, "circuit board-level" electronic additive manufacturing technology uses an additive process to spray or print conductive paste on the surface of an insulating substrate to achieve one-time molding of conductive patterns, providing an efficient and precise solution for the manufacture of electronic components. Conductive paste, as the core material for circuit printing, is usually composed of conductive phase metal powder, adhesive phase polymer resin and other additives.
[0003] Epoxy resin is a commonly used adhesive component in conductive pastes because of its high mechanical properties and chemical stability. In practical applications, due to its high molecular weight, epoxy resin is very easy to become brittle and crack after cross-linking reaction and curing at high temperature, resulting in a sharp drop in adhesion. In order to overcome this problem, it is usually toughened and modified, such as introducing flexible groups between molecular chains, thereby improving the flexibility and bendability of the material, making it more suitable for the manufacture of complex shapes.
[0004] However, the introduction of toughening groups also brings a new challenge, which is that it will reduce the heat resistance of the resin, making the slurry prone to decomposition in high temperature environments, thus affecting the overall performance.
[0005] Therefore, it is very important to develop a flexible conductive paste suitable for high temperature environments. In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a high temperature resistant conductive paste, the research and development difficulty of which mainly lies in the difficulty of taking both the flexibility and heat resistance of the product into consideration at the same time. After exploring and optimizing the key factors affecting the above effects, the present invention provides a high temperature resistant conductive paste and its preparation method and application.
[0007] Specifically, the present invention first provides a conductive paste, which comprises, by weight:
[0008] 10-21 parts of polyurethane resin, 6-16 parts of epoxy resin, and 50-70 parts of conductive powder;
[0009] The conductive powder comprises spherical silver powder and flaky silver powder in a weight ratio of (40-50):(10-20); the particle size of the spherical silver powder is 1-5 μm; the particle size of the flaky silver powder is 1-5 μm.
[0010] The present invention finds that the above scheme is beneficial to simultaneously improve the flexibility and heat resistance of the slurry.
[0011] Those skilled in the art can set other functional components in the formula and parameters in the process according to common knowledge, which can all obtain effects comparable to the above description of the present invention. However, there are also better technical solutions for other components and parameters, for which the present invention further explores and obtains the following preferred solutions.
[0012] Preferably, the polyurethane resin is pre-treated, and the treatment comprises the following steps: mixing the polyurethane resin and the first solvent in a mass ratio of (3-6):(7-15), and then stirring at 80-100°C.
[0013] Furthermore, the polyurethane resin is selected from one or more of 5715, 5703, LR9100, 5836P, and SU-4042.
[0014] Furthermore, the first solvent is selected from one or more of DBE, DEAC, isophorone, dipropylene glycol methyl ether, and diethylene glycol butyl ether.
[0015] Preferably, the epoxy resin is pre-treated, and the treatment comprises the following steps: mixing the epoxy resin and the second solvent in a mass ratio of (2-6):(4-10), and then stirring at 80-100°C.
[0016] Furthermore, the epoxy resin is selected from one or more of 2081, EP1307, GT7071, 1010, and JER1009.
[0017] Furthermore, the second solvent is selected from one or more of DBE, DEAC, isophorone, dipropylene glycol methyl ether, and diethylene glycol butyl ether.
[0018] Preferably, the conductive paste further comprises, by weight: 9-15 parts of liquid polyol resin;
[0019] The liquid polyol resin comprises polyester polyol and polyether polyol in a weight ratio of (8-12):(1-3).
[0020] Furthermore, the polyester polyol is selected from one or more of BMY-600, SR-5586, SD400, and 7250.
[0021] Furthermore, the polyether polyol is selected from one or more of N210, N280, and N330.
[0022] The present invention also found that by using a specifically treated polyurethane resin and epoxy resin as a resin system, supplemented with a specific conductive powder, and adding a liquid polyol resin, the conductive paste can achieve significant improvements in heat resistance, flexibility and adhesion.
[0023] Preferably, the conductive paste further comprises, by weight: 6-9 parts of a curing agent;
[0024] The curing agent is blocked isocyanate.
[0025] Preferably, the conductive paste further comprises, by weight: 0.5-1 part of a rheological agent;
[0026] The rheological agent is selected from one or more of polyurea rheological agents, polyurethane rheological agents and acrylic rheological agents.
[0027] Preferably, the conductive paste further comprises, by weight: 0.5-1 part of a coupling agent;
[0028] The coupling agent is selected from one or more of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.
[0029] Those skilled in the art can combine the above technical solutions according to common sense to obtain preferred embodiments of the conductive paste of the present invention.
[0030] As a preferred embodiment of the present invention, the conductive paste comprises the following components in parts by weight:
[0031] Conductive powder 50-70 parts, polyurethane resin 10-21 parts, epoxy resin 6-16 parts, liquid polyol resin 9-15 parts, curing agent 6-9 parts, rheological agent 0.5-1 parts, coupling agent 0.5-1 parts;
[0032] The conductive powder comprises spherical silver powder and flaky silver powder in a weight ratio of (40-50): (10-20); the particle size of the spherical silver powder is 1-5 μm; the particle size of the flaky silver powder is 1-5 μm; the liquid polyol resin comprises polyester polyol and polyether polyol in a weight ratio of (8-12): (1-3); the curing agent is a blocked isocyanate; the rheological agent is selected from one or more of polyurea rheological agents, polyurethane rheological agents, and acrylic rheological agents; the coupling agent is selected from one or more of silane coupling agents, titanate coupling agents, and aluminate coupling agents.
[0033] In the present invention, the heat resistance of the conductive paste is effectively improved by screening a specific polyurethane resin, and the specific epoxy resin is screened so that the conductive paste forms a complex cross-linked network structure during the curing process, thereby improving the adhesion between the conductive paste and the substrate; at the same time, the addition of liquid polyol resin further improves the degree of reaction cross-linking of the paste, thereby further improving the adhesion; in addition, the conductive powder composed of spherical silver powder with a particle size of 1-5μm and flaky silver powder with a particle size of 1-5μm makes the conductive channel of the paste more diversified and three-dimensional, effectively reduces the resistance and improves the conductive performance; supplemented by a specific curing agent, a rheological agent and a coupling agent, a conductive paste with excellent performance is finally obtained.
[0034] The viscosity of the conductive paste provided by the present invention is 25000-35000 mPa·s.
[0035] The present invention also provides a method for preparing the conductive paste described above, comprising: mixing the components uniformly, and then grinding until the fineness of the mixed material is reduced to less than 5 μm.
[0036] The present invention also finds that the above-mentioned method is used to prepare the conductive paste, which can ensure that the components are mixed evenly and ensure that the product properties do not change differentially.
[0037] In a specific embodiment, grinding is performed using a triple roll mill.
[0038] The present invention also provides the use of the above-mentioned conductive paste in a circuit board, preferably in a flexible circuit board.
[0039] The present invention further provides an electronic device, comprising a substrate and a conductive circuit located on the substrate, wherein the conductive circuit is formed by printing the conductive paste described above and then heating and curing it.
[0040] Preferably, the curing temperature is 180-200° C. and the curing time is 30-60 min.
[0041] Preferably, the printing method is pad printing, screen printing, electrostatic spinning or printing.
[0042] Preferably, the substrate is made of a flexible material, such as PI, PEEK, etc.
[0043] Based on the above scheme, the beneficial effects of the present invention are as follows:
[0044] The present invention obtains a conductive paste with excellent heat resistance, flexibility, adhesion and conductivity by optimizing the formula, which provides a reliable basis for its wide application in the field of flexible electronics.
[0045] Specifically, the conductive circuit made of the conductive paste was immersed in a 288°C tin pool (10 seconds each time, repeated 3 times), and the resistance change rate was less than 1%; it was placed in a 200°C oven and baked continuously for 6 hours without yellowing; the peel strength reached more than 8N / cm; after 100 times of 180° cycle bending test, there was no breakage, and the resistance change rate was less than 5%. DETAILED DESCRIPTION
[0046] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.
[0047] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.
[0048] Example 1
[0049] This embodiment provides a conductive paste, and its formula is as follows:
[0050] Conductive powder 59.8 parts, polyurethane resin 12.5 parts, epoxy resin 7.3 parts, liquid polyol resin 11.1 parts, curing agent 7.8 parts, rheological agent 0.7 parts, coupling agent 0.8 parts;
[0051] in,
[0052] The conductive powder comprises spherical silver powder and flake silver powder in a weight ratio of 45.9:13.9; the particle size of the spherical silver powder is 1-5 μm; the particle size of the flake silver powder is 1-5 μm;
[0053] The polyurethane resin is pre-treated, and the treatment comprises the following steps: 5715 and DBE are mixed in a mass ratio of 4:8.5, and then stirred at 80-100° C. for 24 hours, and cooled to room temperature;
[0054] The epoxy resin is pre-treated, and the treatment comprises the following steps: 2081 and DBE are mixed in a mass ratio of 2.3:5, and then stirred at 80-100° C. for 24 hours, and cooled to room temperature;
[0055] The liquid polyol resin comprises polyester polyol and polyether polyol in a weight ratio of 9.9:1.2; the polyester polyol is BMY-600; the polyether polyol is N210;
[0056] The curing agent is a blocked isocyanate;
[0057] The rheological agent is a polyurea rheological agent;
[0058] The coupling agent is a silane coupling agent.
[0059] This embodiment further provides a method for preparing the conductive paste, which is specifically: mixing the components uniformly, and then grinding them with a three-roll grinder until the fineness of the mixed material is reduced to less than 5 μm.
[0060] Example 2
[0061] This embodiment provides a conductive paste, and its formula is as follows:
[0062] Conductive powder 57.2 parts, polyurethane resin 13.1 parts, epoxy resin 8.2 parts, liquid polyol resin 12.1 parts, curing agent 7.8 parts, rheological agent 0.8 parts, coupling agent 0.8 parts;
[0063] in,
[0064] The conductive powder comprises spherical silver powder and flake silver powder in a weight ratio of 45:12.2; the particle size of the spherical silver powder is 1-5 μm; the particle size of the flake silver powder is 1-5 μm;
[0065] The polyurethane resin is pre-treated, and the treatment comprises the following steps: 5703 and DEAC are mixed in a mass ratio of 4.1:9, and then stirred at 80-100° C. for 24 hours, and cooled to room temperature;
[0066] The epoxy resin is pre-treated, and the treatment comprises the following steps: EP1307 and DEAC are mixed in a mass ratio of 2.5:5.7, and then stirred at 80-100° C. for 24 hours, and cooled to room temperature;
[0067] The liquid polyol resin comprises polyester polyol and polyether polyol in a weight ratio of 10.5:1.6; the polyester polyol is SR-5586; the polyether polyol is N280;
[0068] The curing agent is a blocked isocyanate;
[0069] The rheological agent is a polyurethane rheological agent;
[0070] The coupling agent is a titanate coupling agent.
[0071] This embodiment further provides a method for preparing the conductive paste, which is specifically: mixing the components uniformly, and then grinding them with a three-roll grinder until the fineness of the mixed material is reduced to less than 5 μm.
[0072] Example 3
[0073] This embodiment provides a conductive paste, and its formula is as follows:
[0074] Conductive powder 59.3 parts, polyurethane resin 13.2 parts, epoxy resin 8.2 parts, liquid polyol resin 10.9 parts, curing agent 6.8 parts, rheological agent 0.8 parts, coupling agent 0.8 parts;
[0075] in,
[0076] The conductive powder includes spherical silver powder and flake silver powder in a weight ratio of 44.8:14.5; the particle size of the spherical silver powder is 1-5 μm; the particle size of the flake silver powder is 1-5 μm;
[0077] The polyurethane resin is pre-treated, and the treatment comprises the following steps: LR9100 and isophorone are mixed in a mass ratio of 4:9.2, and then stirred at 80-100° C. for 24 hours, and cooled to room temperature;
[0078] The epoxy resin is pre-treated, and the treatment comprises the following steps: GT7071 and isophorone are mixed in a mass ratio of 2.9:5.3, and then stirred at 80-100° C. for 24 hours, and cooled to room temperature;
[0079] The liquid polyol resin comprises polyester polyol and polyether polyol in a weight ratio of 9.5:1.4; the polyester polyol is SD400; the polyether polyol is N330;
[0080] The curing agent is a blocked isocyanate;
[0081] The rheological agent is an acrylic rheological agent;
[0082] The coupling agent is an aluminate coupling agent.
[0083] This embodiment further provides a method for preparing the conductive paste, which is specifically: mixing the components uniformly, and then grinding them with a three-roll grinder until the fineness of the mixed material is reduced to less than 5 μm.
[0084] Example 4
[0085] This embodiment provides a conductive paste, and its formula is as follows:
[0086] Conductive powder 58 parts, polyurethane resin 11.1 parts, epoxy resin 9.9 parts, liquid polyol resin 12 parts, curing agent 7.6 parts, rheological agent 0.7 parts, coupling agent 0.7 parts;
[0087] in,
[0088] The conductive powder comprises spherical silver powder and flake silver powder in a weight ratio of 46:12; the particle size of the spherical silver powder is 1-5 μm; the particle size of the flake silver powder is 1-5 μm;
[0089] The polyurethane resin is pre-treated, and the treatment comprises the following steps: 5836P and dipropylene glycol methyl ether are mixed in a mass ratio of 3.6:7.5, and then stirred at 80-100° C. for 24 hours, and cooled to room temperature;
[0090] The epoxy resin is pre-treated, and the treatment comprises the following steps: 1010 and dipropylene glycol methyl ether are mixed in a mass ratio of 3.5:6.4, and then stirred at 80-100° C. for 24 hours, and cooled to room temperature;
[0091] The liquid polyol resin comprises polyester polyol and polyether polyol in a weight ratio of 10.1:1.9; the polyester polyol is 7250; the polyether polyol is N280;
[0092] The curing agent is a blocked isocyanate;
[0093] The rheological agent is a polyurea rheological agent;
[0094] The coupling agent is a titanate coupling agent.
[0095] This embodiment further provides a method for preparing the conductive paste, which is specifically: mixing the components uniformly, and then grinding them with a three-roll grinder until the fineness of the mixed material is reduced to less than 5 μm.
[0096] Example 5
[0097] This embodiment provides a conductive paste, and its formula is as follows:
[0098] Conductive powder 58.8 parts, polyurethane resin 10.9 parts, epoxy resin 9.7 parts, liquid polyol resin 11.8 parts, curing agent 7.5 parts, rheological agent 0.7 parts, coupling agent 0.7 parts;
[0099] in,
[0100] The conductive powder includes spherical silver powder and flake silver powder in a weight ratio of 44.2:14.6; the particle size of the spherical silver powder is 1-5 μm; the particle size of the flake silver powder is 1-5 μm;
[0101] The polyurethane resin is pre-treated, and the treatment comprises the following steps: SU-4042 and diethylene glycol butyl ether are mixed in a mass ratio of 3.6:7.3, and then stirred at 80-100° C. for 24-48 hours, and cooled to room temperature;
[0102] The epoxy resin is pre-treated, and the treatment comprises the following steps: JER1009 and diethylene glycol butyl ether are mixed in a mass ratio of 3.4:6.3, and then stirred at 80-100° C. for 24 hours, and cooled to room temperature;
[0103] The liquid polyol resin comprises polyester polyol and polyether polyol in a weight ratio of 9.9:1.9; the polyester polyol is BMY-600; the polyether polyol is N210;
[0104] The curing agent is a blocked isocyanate;
[0105] The rheological agent is an acrylic rheological agent;
[0106] The coupling agent is an aluminate coupling agent.
[0107] This embodiment further provides a method for preparing the conductive paste, which is specifically: mixing the components uniformly, and then grinding them with a three-roll grinder until the fineness of the mixed material is reduced to less than 5 μm.
[0108] Comparative Example 1
[0109] This comparative example provides a conductive paste, which is different from Example 1 in that, in the formula, the amount of conductive powder is 40 parts by weight, the amount of polyurethane resin is 26 parts by weight, and the amount of epoxy resin is 13.6 parts by weight.
[0110] Comparative Example 2
[0111] This comparative example provides a conductive paste, which is different from Example 1 in that, in the formula, the conductive powder includes spherical silver powder and flake silver powder in a weight ratio of 15.1:44.7.
[0112] Comparative Example 3
[0113] This comparative example provides a conductive paste, which is different from Example 1 in that no liquid polyol resin is added in the formula.
[0114] Test example
[0115] In this test example, the viscosity of the conductive paste of each embodiment and comparative example was first tested using a viscosity tester, and then the conductive paste of each embodiment and comparative example was respectively formed into a conductive circuit on the surface of a 25 μm thick PI film by screen printing (the printability of each conductive paste was observed during the printing process), and then cured at 190° C. for 40 minutes to obtain several flexible circuit boards, and then the performance of each flexible circuit board was tested, as follows:
[0116] 1. Perform square resistance test on each flexible circuit board respectively. The specific test method is: use a resistance tester to detect the resistance, and then calculate it into square resistance.
[0117] 2. Conduct adhesion test on the conductive circuits on each flexible circuit board respectively. The specific test method is: use 3M600# adhesive tape to adhere to the surface of the conductive circuit. After standing for 1 minute, use external force to quickly remove the 3M 600# adhesive tape and observe whether the appearance of each conductive circuit is falling off; if there is no falling off, the adhesion is good; if there is falling off (including partial falling off), the adhesion is poor.
[0118] 3. Conduct temperature resistance test on each flexible circuit board respectively. The specific test method is: place the flexible circuit board in a tin pool at 288°C for 3 times, each time for 10 seconds, and observe whether each conductive circuit is melted; if there is no melting, it means that the temperature resistance is good; if melting occurs (including partial melting), it means that the temperature resistance is poor.
[0119] 4. Perform a bending test on each flexible circuit board. The specific test method is: bend the flexible circuit board 180° around the core axis, cycle 100 times, and calculate the resistance change rate.
[0120] 5. Perform peel strength tests on each flexible circuit board separately. The specific test method is: use a universal tensile testing machine for testing.
[0121] 6. The test results are shown in Table 1.
[0122] Table 1 Test results
[0123]
[0124]
[0125] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A conductive paste, characterized in that: By weight, it includes: 10-21 parts of polyurethane resin, 6-16 parts of epoxy resin, and 50-70 parts of conductive powder; The conductive powder comprises spherical silver powder and flaky silver powder in a weight ratio of (40-50):(10-20); the particle size of the spherical silver powder is 1-5 μm; the particle size of the flaky silver powder is 1-5 μm.
2. The conductive paste according to claim 1, characterized in that: The polyurethane resin is pre-treated, and the treatment comprises the following steps: mixing the polyurethane resin and the first solvent in a mass ratio of (3-6): (7-15), and then stirring at 80-100° C.; Preferably, the polyurethane resin is selected from one or more of 5715, 5703, LR9100, 5836P, and SU-4042; More preferably, the first solvent is selected from one or more of DBE, DEAC, isophorone, dipropylene glycol methyl ether, and diethylene glycol butyl ether.
3. The conductive paste according to claim 1 or 2, characterized in that: The epoxy resin is pre-treated, and the treatment comprises the following steps: mixing the epoxy resin and the second solvent in a mass ratio of (2-6): (4-10), and then stirring at 80-100° C.; Preferably, the epoxy resin is selected from one or more of 2081, EP1307, GT7071, 1010, and JER1009; More preferably, the second solvent is selected from one or more of DBE, DEAC, isophorone, dipropylene glycol methyl ether, and diethylene glycol butyl ether.
4. The conductive paste according to any one of claims 1 to 3, characterized in that: In parts by weight, the conductive paste further comprises: 9-15 parts of liquid polyol resin; The liquid polyol resin comprises polyester polyol and polyether polyol in a weight ratio of (8-12):(1-3); Preferably, the polyester polyol is selected from one or more of BMY-600, SR-5586, SD400, and 7250; More preferably, the polyether polyol is selected from one or more of N210, N280 and N330.
5. The conductive paste according to any one of claims 1 to 4, characterized in that: In parts by weight, the conductive paste further comprises: 6-9 parts of a curing agent; The curing agent is blocked isocyanate.
6. The conductive paste according to any one of claims 1 to 5, characterized in that: In parts by weight, the conductive paste further comprises: 0.5-1 part of a rheological agent; The rheological agent is selected from one or more of polyurea rheological agents, polyurethane rheological agents and acrylic rheological agents.
7. The conductive paste according to any one of claims 1 to 6, characterized in that: In parts by weight, the conductive paste further comprises: 0.5-1 part of a coupling agent; The coupling agent is selected from one or more of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.
8. The method for preparing the conductive paste according to any one of claims 1 to 7, characterized in that: include: The components are mixed evenly and then ground until the fineness of the mixed material is reduced to below 5 μm.
9. Use of the conductive paste according to any one of claims 1 to 7 in a circuit board, preferably in a flexible circuit board.
10. An electronic device comprising a substrate and a conductive circuit located on the substrate, characterized in that: The conductive circuit is formed by printing the conductive paste according to any one of claims 1 to 7 and heating and curing; Preferably, the curing temperature is 180-200°C and the curing time is 30-60min; More preferably, the printing method is pad printing, screen printing, electrostatic spinning or printing; Most preferably, the material of the substrate is a flexible material.